Phylogenetic relatedness of food plants reveals highest insect herbivore specialization at intermediate temperatures along a broad climatic gradient - König, Sebastian; Krauss, Jochen; Keller, Alexander; Bofinger, Lukas; Steffan‐Dewenter, Ingolf (Global change biology, 2022)
The composition and richness of herbivore and plant assemblages change along climatic gradients, but knowledge about associated shifts in specialization is scarce and lacks controlling for the abundance and phylogeny of interaction partners. Thus, we aimed to test whether the specialization of phytophagous insects in insect‐plant interaction networks decreases toward cold habitats as predicted by the ‘altitude niche‐breadth hypothesis’ to forecast possible consequences of interaction rewiring under climate change. We used a non‐invasive, standardized metabarcoding approach to reconstruct dietary relationships of Orthoptera species as a major insect herbivore taxon along a broad temperature gradient (~12°C) in Southern Germany. Based on Orthoptera surveys, feeding observations, collection of fecal pellets from >3,000 individuals of 54 species, and parallel vegetation surveys on 41 grassland sites, we quantified plant resource availability and its use by herbivores. Herbivore assemblages were richer in species and individuals at sites with high summer temperatures, while plant richness peaked at intermediate temperatures. Corresponding interaction networks were most specialized in warm habitats. Considering phylogenetic relationships of plant resources, however, the specialization pattern was not linear but peaked at intermediate temperatures, mediated by herbivores feeding on a narrow range of phylogenetically related resources. Our study provides empirical evidence of resource specialization of insect herbivores along a climatic gradient, demonstrating that resource phylogeny, availability, and temperature interactively shape the specialization of herbivore assemblages. Instead of low specialization levels only in cold, harsh habitats, our results suggest increased generalist feeding due to intraspecific changes and compositional differences at both ends of the microclimatic gradient. We conclude that this nonlinear change of phylogeny‐based resource specialization questions predictions derived from the ‘altitude‐niche breadth hypothesis’ and highlights the currently limited understanding of how plant‐herbivore interactions will change under future climatic conditions. The specialization of phytophagous insects changes along climatic gradients, but empirical evidence of how the phylogeny and availability of resources modulate herbivore specialization is scarce. We surveyed plant and orthopteran assemblages on 41 grasslands and reconstructed dietary relationships using metabarcoding of fecal samples and feeding observations. Plant phylogeny, availability, and temperature interactively shaped the specialization of herbivore assemblages, with more generalized assemblages at both ends of the sampled climatic gradient due to intraspecific changes and compositional differences. The nonlinear change of resource specialization highlights the currently limited understanding of how plant‐herbivore interactions will change under future climatic conditions.